2015
DOI: 10.1097/ftd.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Valproic Acid in Adult Chinese Epileptic Patients and its Application in an Individualized Dosage Regimen

Abstract: A PPK model was developed to estimate the individual clearance for patients taking VPA and could be applied for individualizing doses in the target population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 40 publications
(30 reference statements)
4
19
1
5
Order By: Relevance
“…Table summarizes the characteristics of each study. Most of the models were developed in patients with epilepsy . One study reported a model incorporating data from both epileptic and psychiatric patients .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table summarizes the characteristics of each study. Most of the models were developed in patients with epilepsy . One study reported a model incorporating data from both epileptic and psychiatric patients .…”
Section: Resultsmentioning
confidence: 99%
“…The VPA doses of the included studies ranged from 2.4 to 87.9 mg kg À1 d À1 . Use of sustained-release formulation was reported in nine studies [21,28,31,34,37,38,[40][41][42]. Fluorescence polarization immunoassay (FPIA) and enzyme multiplied immunoassay (EMIT) were used in 57.7% and 15.4% of the studies, respectively.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…During backward elimination, the significance of the covariates was confirmed by removing a single covariate at a time from the full model and required an increase in the OFV of at least 6.63 (χ 2 , P <.01,df=1) to remain in the model. An additional criterion for the retention of a covariate in the model was a reduction in unexplained inter‐individual variability and improvement in the precision of the parameter estimates …”
Section: Methodsmentioning
confidence: 99%
“…For more than 4 decades VPA stipulate in clinical practice as an anticonvulsant to control seizures in forms of tonic-clonic (grand mal), complex partial and juvenile myoclonic. Published report by International League Against Epilepsy (ILAE) authorizes the efficiency and value of ethosuximide and VPA for children with absence seizures as initial monotherapy [2][3][4][5][6][7][8][9][10][11][12]. Karlov et al [11] reported a prescription based on valproate in dose 15 -25 mg/kg/day and levetiracetam in dose 20 -25 mg/kg/day that were used in the treatment of 23 patients with juvenile myoclonic, juvenile absence, and convulsive idiopathic generalized and children absence epilepsy.…”
Section: Resultsmentioning
confidence: 99%